4(-x+2)=-(x-4)

Simple and best practice solution for 4(-x+2)=-(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(-x+2)=-(x-4) equation:



4(-x+2)=-(x-4)
We move all terms to the left:
4(-x+2)-(-(x-4))=0
We add all the numbers together, and all the variables
4(-1x+2)-(-(x-4))=0
We multiply parentheses
-4x-(-(x-4))+8=0
We calculate terms in parentheses: -(-(x-4)), so:
-(x-4)
We get rid of parentheses
-x+4
We add all the numbers together, and all the variables
-1x+4
Back to the equation:
-(-1x+4)
We get rid of parentheses
-4x+1x-4+8=0
We add all the numbers together, and all the variables
-3x+4=0
We move all terms containing x to the left, all other terms to the right
-3x=-4
x=-4/-3
x=1+1/3

See similar equations:

| -x-2(0)=2 | | 4y=-24y= | | -24=2(x-7)+6 | | 2c-12+7c=5-3c+6 | | 2(n+8)-3n=8 | | 4(x-7)-3x=-7 | | -3(x-2)=-4(2x-1) | | 3x−15+6x+2=45 | | 6(x-2)=-2(2x+5) | | 1/2u-2/3=4/5u+1 | | 2-2x=917 | | 17=9(2-2x) | | 40+(2x)=8 | | -14n=252 | | -0+2y=6 | | 4/x-12=24 | | 5^3x=12 | | 1.50r=8.95=26.95 | | 10+v=-3-2 | | 4x-4-2x+6=40-8 | | -36y=36 | | 3/2=1/6w | | -2x-4=1/2x-5 | | -6-3x+6x+16=31 | | 3x-8(2x+3)=8(2x+5) | | x-1025=2541 | | 3(v+4)=-6(3v-1)+9v | | 6x=6x+3-3 | | 7-3b+b2=8 | | 3x-18-5x-50=24 | | -6(w+2)=4w-7+2(4w+5) | | -3(-8v+4)-7v=3(v-3)-7 |

Equations solver categories